Synergistic activity of Pitstop-2 and 1,6-hexanediol in aggressive human lung cancer cells - Sílvio Terra Stefanello; Caren Rigon Mizdal; Aline Franzen da Silva; Luca Matteo Todesca; Félix Alexandre Antunes Soares; Victor Shahin (Discover Nano)
Abstract Metastatic cancer cells undergo metabolic reprogramming, which involves changes in the metabolic fluxes, including endocytosis, nucleocytoplasmic transport, and mitochondrial metabolism, to satisfy their massive demands for energy, cell division, and proliferation compared to normal cells. We have previously demonstrated the ability of two different types of compounds to interfere with linchpins of metabolic reprogramming, Pitstop-2 and 1,6-hexanediol (1,6-HD). 1,6-HD disrupts glycolysis enzymes and mitochondrial function, enhancing reactive oxygen species production and reducing cellular ATP levels, while Pitstop-2 impedes clathrin-mediated endocytosis and small GTPases activity. Besides, both compounds interfere with the integrity of nuclear pore complexes, the gatekeepers for all nucleocytoplasmic transport. Herein, we investigate the possible synergistic effects of both compounds on lowly, highly metastatic, and erlotinib-resistant non-small cell lung cancer. We observe a synergistic cytotoxic effect on erlotinib-resistant cells. Moreover, motility assays show that the compounds combination significantly impedes the motility of all cells. Drug safety and tolerability assessments were validated using the in vivo model organism Caenorhabditis elegans, where fairly high doses showed negligible impact on survival, development, or behavioral parameters. Our findings propose that the 1,6-HD and Pitstop-2 combination may usher in the design of potent strategies for treating advanced lung cancer.